Codification of Criminal Law: Guided by Xi Jinpings thought on the Rule of Law - Feng, Jiaqi (International Journal of Social Sciences and Public Administration, 2025)
Under the background of the new era, the problem of codification of criminal law in China is becoming increasingly prominent. The legislative concept and legislative mode of the codification of criminal law are also further put forward higher requirements. Under the guidance of Xi Jinpings thought on the rule of law, a series of issues such as whether the codification should be carried out and how still need to be deeply studied. Therefore, from the significance of criminal law codification, realistic basis, influence on society and legislative concept of research.